Negara, Agama, dan Legislasi Daerah: Dinamika Perda di Kota Tasikmalaya - Zahra, Maghfira Aulia; Maulana, Arif; Novian, Karina (Institut Agama Islam Negeri Kerinci, 2024)
The debate over religion-based regional regulations (perda) has become a significant discourse in studies of state–religion relations at the local level, particularly within the context of democracy and societal pluralism. This article aims to analyze the dynamics of the implementation of Regional Regulation No. 12 of 2009 and its revision through Regional Regulation No. 7 of 2014 in Tasikmalaya City, a region known for its religious character and Muslim-majority population. This study employs a descriptive qualitative method using document study and policy discourse analysis approaches. The findings reveal that Regional Regulation No. 12 of 2009 sparked controversy due to its perceived discriminatory nature against minority groups and its lack of procedural legislative rigor, which led to ineffective implementation. The revision in Regional Regulation No. 7 of 2014 demonstrates a shift toward more inclusive language and editorial format, yet it retains ideological elements that favor the dominant religious majority. These findings highlight the ambivalence that arises when moral aspirations of the community are formalized into local policy, potentially conflicting with constitutional principles. This study contributes to a deeper understanding of identity politics in subnational legislation.